Parenting Research in Indonesia: What We Have Done So Far - Beatriks Novianti Kiling-Bunga; Kristin Margiani; Indra Yohanes Kiling (Buletin Psikologi, 2020)
Parenting is one of the most important responsibilities that someone could bear as a parent, probably the most burdensome too. Regardless, several questions are still left unanswered by Indonesian scientists, what are the field of studies related to parenting? What are the problems emanating from the practice of parenting and their solutions? What are the strategic steps one can take as psychology scientist or practitioner to improve parenting in Indonesia? This study examined the application of scoping review to provide responses for aforementioned questions. Just like the way a cartographer map an area in order to advance civilization, a scoping review is meant to enlighten future researchers with the answers on “what has been done?”. Five databases were searched in this review, 94 articles were discovered to undergo further rigorous selection, and 16 chosen articles were charted and analyzed accordingly. Finding shows that education, health, and psychology were the field of studies associated with high quality parenting research in Indonesia. Problems in child’s development caused by bad parenting attracted most researchers’ attention. Solutions provided were unique to each study’s context and hard to generalize. Finally, it is suggested that psychologists’ involvement in national parenting program is inevitable, and should start from today.